Trauma and Adolescents - Ashley Eckes; Heidi Liss Radunovich (EDIS)
FCS2280, a 5-page fact sheet by Ashley Eckes and Heidi Liss Radunovich, explores the special needs of adolescents coping with trauma, tragedy, and disaster. It explains why teens may be especially vulnerable to trauma and its effects and gives tips to help teens cope with and process trauma. Includes a section on PTSD. Published by the UF Department of Family, Youth and Community Sciences, October 2007.